Career preferences of Filipino senior high school students - Chery Fernandez; Meshel Balijon; Inero Ancho (CTU Journal of Innovation and Sustainable Development)
This research determined the trends and challenges in career preferences of the public high schools in Cebu City, Philippines. The study participants were 35 students, including five guidance counselors and advocates (GCA) from different identified public national high schools. This research used a quantitative-qualitative mixed design through a focused group discussion to confirm the responses of the respondents. The results show that students often choose careers that suit the needs of their families. Sometimes, they use Facebook, LinkedIn, Twitter, and My Space to seek a job, base their choices in popular courses/degrees today, they even use technology to do that or choose a career that fits their abilities. According to the GCAs, most of the students lack motivation and do not know the deeper reasons for the courses that they want and just pick a degree program just for the sake of having one.  Sometimes, they lack information about different careers, base things on practicality, they cannot decide, they do not have a choice and their parents choose their career for them. The findings suggest GCAs need to encourage learners, and their parents to make use of a career pathing design for them to be guided in terms of their career decisions.